Criminal justice and the Catholic Church - Skotnicki, Andrew (Rowman & Littlefield Publishers, 2008)
What is the prison and who is the prisoner? -- The justification of punishment -- The end of punishment -- Prison as the normative means of punishment -- The prison and secular society -- A Catholic theory of criminal justice